Investigating the Relationship of Work Errors with Occupational Stress and Perceived Organizational Support Among nurses: A Descriptive Correlational Study - Zahra Bolghar; Esfandyar Baljani; Hossein Habibzadeh; Monireh Rezaee Moradali (Zanjan University of Medical Sciences and Health Services, 2023)
Background: Occupational stress in nurses leads to job burnout and an increase in missed nursing care, and the incidence of work errors. Investigating the factors associated with occupational stress can assist nursing managers in supporting nurses, reducing and handling errors, and adopting appropriate policies. Objectives: This study aimed to determine the relationship between work errors and stress sources, and perceived organizational support among nurses. Methods: This was a correlational descriptive study conducted on 160 nurses working at the hospitals of Miandoab City, Western Azerbaijan province of Iran. The nurses were enrolled by the census from April to July 2019. The data collection tool was a 4-part questionnaire for recording demographic information, nurses' sources of stress, perceived organizational support, and nursing work errors. The data were analyzed by SPSS21 software. Results: Most of the nurses were female (61.8%), had a work experience of fewer than three years (43.75%), and had a bachelor's degree (73.1%). The sources of stress were directly and significantly correlated with nursing errors in the dimensions of drug therapy (r=0.241, p=0.002), nursing care (r=0.685, p=0.014), and report writing (r=0.101, p=0.030). Also, perceived organizational support was significantly and inversely associated with nursing errors in the dimensions of nursing care (r = -0.190, p=0.016) and drug therapy (r = -0.182, p=0.042). Sources of stress, along with perceived organizational support, years of service, and the level of education, explained 8% of variations in nursing work errors. Conclusion: The results of the study showed that an increase in the sources of stress and a decrease in perceived organizational support was related to a rise in work errors among nurses. These two factors, along with years of service and level of education, were among the predictors of nursing work errors. Therefore, it is suggested to pay attention to organizational support and manage stress sources in the work environment to reduce nurses' work errors.